Association between parents’ smoking status and tobacco exposure in school-age children: assessment using major urine biomarkers - Sung Hoon Jeong (Nature Portfolio, 2021)
Abstract Children are at risk of exposure to secondhand smoke. We aimed to evaluate the extent of their exposure to it in relation to their parents’ smoking status by using biomarkers relevant to smoking. We evaluated 847 school-age children (6–12 years) who lived with their parents, using data from the Korea National Health and Nutrition Examination Survey 2016–2018. Secondhand smoke exposure in children of non-smoking and smoking parents was assessed by measuring urinary 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) and cotinine concentrations. Overall, the parents of 482 (55.1%) children smoked and those of 392 (44.9%) children did not smoke. After adjusting for covariates, significantly higher concentrations of NNAL (β = 0.482, standard error [S.E.] = 0.065, P < 0.001) and cotinine (β = 0.472, S.E. = 0.06, P < 0.001) were found in children of smoking parents than in children of non-smoking parents. Children of parents who smoked a higher number of cigarettes showed higher NNAL and cotinine concentrations than children of non-smoking parents. Children with both parents who smoked showed the highest NNAL and cotinine concentrations. Children of smoking parents are at a higher risk of exposure to secondhand smoke. A smoke-free environment must be maintained to protect children from the harmful effects of secondhand smoke. Therefore, comprehensive national anti-smoking policies are required.